The theoretical and scientific problems of damasio’s conceptual model of consciousness - Rosa, Luiz Augusto [UNESP] (My University, 2017)
Here I assess Damasio’s conceptual model of consciousness based mainly on the concepts of emotion, feeling, and consciousness by analyzing its conceptual implications and its theoretical and scientific problems. One of the conceptual implications of the direct interaction between the concept of “feeling” and the concept of “consciousness” is the concept of consciousness as “feeling a feeling”, which is also recognized by Damasio. The concept “feeling a feeling” directly implies the concept of consciousness as “an emotional perception of an emotional perception”. Each implication has further theoretical implications that form a web of theoretical and scientific problems. I also argue that, since Damasio’s model of consciousness is a neuroscientific model, it should provide a rigorous integration between the high-order concepts and the empirical concepts that underlie them, which, for example, is the case of Dehaene’s model of consciousness. Moreover, at the end of the paper, I suggest some conceptual changes that would minimize the theoretical problems of Damasio’s conceptual model of consciousness.
Keywords: Conceptual model; Consciousness; Damasio; Philosophy of neuroscience; Philosophy of Science; Theoretical problems